Los primeros mestizos americanos: ¿un grupo social marginado? Defensa del protagonismo socio-político de la primera generación de mestizos del Nuevo Reino de Granada, siglos XVI-XVII - Shems Kasmi (Nuevo mundo - Mundos Nuevos, 2023)
Americanist historiography, even very recently, has tended to consider that the trajectory of the first American mestizos was often characterized by forms of marginalization. However, in our in-depth study of the case of the New Kingdom of Granada between 1537 and 1615, we have found that the dominant tendency did not necessarily correspond to this traditional view, and that, on the contrary, their socio-political performance was characterized by a strong protagonism in the sixteenth century. In the present work we will show what that protagonism consisted of, in order to qualify two common places associated with the mestizos: the idea that they were not well integrated into the Hispanic-Creole group, and the idea that they were generally kept in subordinate positions, playing a secondary historical role. Thus, we show here, on the contrary, how they were generally authentic members of the Hispanic-criollo group and its sociability networks, and how they came to exert great power and influence due to the interstitial position they occupied.